Pengaruh Naungan Terhadap Pertumbuhan dan Produktivitas Padi Ladang Kabupaten Deli Serdang, Sumatera Utara - Noverina Chaniago; Irfan Suliansyah; Irawati Chaniago; Nalwida Rozen (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2022)
One of the factors hindering the development of upland rice cultivation among annual crops is the limited number of shade-tolerant upland rice varieties. It is very important to assemble shade-tolerant upland rice varieties with high yields. The purpose of the study was to determine the effect of shade on the growth and productivity of five genotypes of upland rice. This research was carried out in the experimental garden of the Faculty of Agriculture, the Islamic University of North Sumatra with an altitude of 25 m above sea level, from June to December 2020. The research design was split-plot and repeated three times. The main plot of shade treatment consisted of two levels, namely no shade (0%) and shade treatment (70%). The sub-plots were five genotypes of upland rice in Deli Serdang and two shade-tolerant varieties. Shade treatment affected the growth and productivity of five genotypes of upland rice in Deli Serdang District (Sialus, Arias, Ramos Merah, Silayur, and Sirabut) and two shade-tolerant varieties (Rindang 1 and 2). Two genotypes of upland rice were obtained, namely Silayur and Sirabut which were more shade tolerant, based on flowering age, harvest age, and grain weight per clump. When compared with Rindang 1 and 2 varieties, the two genotypes of upland rice were the same or more tolerant.